Rediscovering Love: Mengatasi Konflik Pernikahan dengan Memahami Inner Child - Mona Lahdji; Riana Sahrani; P. Tommy Y. S. Suyasa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Unresolved marital conflicts often lead to divorce, with childhood trauma or the "inner child" being one of the main underlying causes. The webinar "Rediscovering Love: Overcoming Marital Conflict by Realizing The Inner Child" aimed to provide psychological education to couples to help them recognize and heal their inner child in order to effectively manage marital conflicts. This program integrated three key steps: (1) healing the inner child, (2) managing emotions and negative thought patterns, and (3) developing positive communication skills. Based on pre-test and post-test results, participants showed a significant increase in understanding the impact of childhood trauma on marital conflict, as well as their readiness to apply new communication and emotional management skills. This webinar proved effective in strengthening participants' understanding and skills in addressing marital challenges, while paving the way for healthier and more harmonious relationships.